Integrative transcriptomics and proteomics analysis provide a deep insight into goose astrovirus-host interactions during GAstV infection - Jianzhou Shi; Qianyue Jin; Jinbing Zhao; Jinran Yu; Xianyi Yu; Guirong Sun; Lunguang Yao (Poultry Science)
ABSTRACT: Goose astrovirus (GAstV) is a newly discovered astrovirus. GAstV causes gout and death in 4- to -16-day-old goslings. For the past few years, fatal gout, the cardinal clinical symptom of gosling infected with GAstV, has been spreading rapidly in some goose Chinese farms, which caused continuous economic losses to the goose breeding industry in China. Currently, several underlying mechanisms involved in viral replication, inflammatory reaction, virions release, and viral pathogenesis of GAstV remain to be elucidated. In this study, we explored the mechanisms of GAstV-host interactions, the transcriptome and proteome profiles of GAstV-infected LMH cells were sequenced by RNA-seq and data-independent acquisition (DIA) techniques, respectively, and followed using an integrative analysis. Compared with uninfected LMH cells, a total of 322 differentially expressed genes (DEG) (195 up-regulated, 127 down-regulated) and 36 differentially expressed proteins (DEP) (31 up-regulated, 5 down-regulated) were detected. Nine DEGs were randomly selected for further validation by quantitative real-time polymerase chain reaction (qPCR). Through GO and KEGG enrichment analysis, DEG and DEP were significantly enriched in several important cellular signaling pathways, including MAPK, PI3K-Akt, cAMP, chemokine, calcium, phospholipase D, Ras, TNF, IL-17, Rap1, NF-kappa B signaling pathways, indicating that GAstV affects cell growth and immune signaling. This study provided an overview of changes in transcriptome and proteome profiles of GAstV-infected LMH cells, therefore, providing a crucial basis to further explore the mechanisms of GAstV-host interactions.